Brain drain in Emergency Medicine in Lebanon, building locally and exporting globally - Eveline Hitti; Sarah S. Abdul-Nabi; Afif Mufarrij; Amin Kazzi (BMC Medical Education)
Abstract Objective Despite the growth of Emergency Medicine (EM) globally, shortages of EM-trained physicians persist in many countries, disproportionately affecting lower middle/low-income countries (LMIC/LIC). This study examines the career paths of graduates of an Emergency Medicine residency-training program established in Lebanon with the aim of building local capacity in EM. Design and patients This descriptive study utilizes secondary data sourced from an alumni database that includes nine cohorts of graduates from an Emergency Medicine residency program at the American University of Beirut Medical Center in Lebanon. Measurements and main results Within 12 years since the EM residency program establishment a total of 9 cohorts, including 44 physicians had completed their residency training in EM, with 40.9% being female and 95.5% Lebanese citizens. After graduation, almost half of our graduates (47.7%) enrolled in fellowship training programs and 40.9% joined the workforce. Fellowships in Trauma (19%) and Oncologic Emergencies (19%) were the most commonly pursued. Initial employment destinations predominantly included Lebanon, the United Arab Emirates and the Kingdom of Saudi Arabia, (61.1, 33.3 and 5.6% respectively). However, retention within the local market declined with time, with a median time spent in Lebanon of 1 year and a mean of 3.3 years of practice in Lebanon prior to emigration. Presently, graduates are mostly dispersed across the Gulf Cooperation Council region (38.6%), the USA (25%), and Lebanon (20.5%). Conclusion Building Emergency Medicine expertise to match the growing population needs for specialized acute care remains a challenge globally, especially in low-middle income and low-income countries. Our study highlights the challenge of retaining specialized medical graduates in LMIC. Understanding and addressing the root-causes of out-migration of highly specialized medical workforce is an essential component of addressing local workforce challenges that needs to be coupled with capacity building initiatives for meaningful impact.